The effect of preprocessing pipelines in subject classification and detection of abnormal resting state functional network connectivity using group ICA - Vergara, Victor M.; Mayer, Andrew R.; Damaraju, Eswar; Hutchison, Kent; Calhoun, Vince D. (NeuroImage (Orlando, Fla.), 2017)
Resting state functional network connectivity (rsFNC) derived from functional magnetic resonance (fMRI) imaging is emerging as a possible biomarker to identify several brain disorders. Recently it has been pointed out that methods used to preprocess head motion variance might not fully remove all unwanted effects in the data. Proposed processing pipelines locate the treatment of head motion effects either close to the beginning or as one of the final steps. In this work, we assess several preprocessing pipelines applied in group independent component analysis (gICA) methods to study the rsFNC of the brain. The evaluation method utilizes patient/control classification performance based on linear support vector machines and leave-one-out cross validation. In addition, we explored group tests and correlation with severity measures in the patient population. We also tested the effect of removing high frequencies via filtering. Two real data cohorts were used: one consisting of 48 mTBI and one composed of 21 smokers, both with their corresponding matched controls. A simulation procedure was designed to test the classification power of each pipeline. Results show that data preprocessing can change the classification performance. In real data, regressing motion variance before gICA produced clearer group differences and stronger correlation with nicotine dependence. •We analyze different preprocessing pipelines for group independent component analysis (gICA).•Pipelines were evaluated using classification algorithms, cross validation and statistical methods.•The data pinpoint a strategy that best seems to prepare fMRI data for gICA.